2021
DOI: 10.3174/ajnr.a7244
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hippocampal Subfield Segmentation Agreement between 2 Automated Protocols across the Adult Life Span

Abstract: BACKGROUND AND PURPOSE:The hippocampus is a frequent focus of quantitative neuroimaging research, and structural hippocampal alterations are related to multiple neurocognitive disorders. An increasing number of neuroimaging studies are focusing on hippocampal subfield regional involvement in these disorders using various automated segmentation approaches. Direct comparisons among these approaches are limited. The purpose of this study was to compare the agreement between two automated hippocampal segmentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Second, volume measurement using MRI has a possible inherent bias of over-or underestimation in term of precise delineation and quantification. The ranges of the hippocampal subfield volumes acquired by the Winterburn atlas in this study might be different from previous data obtained by manual segmentation, owing to labeling protocol differences [36]. Third, the relatively small number of patients could affect the power of the study to detect all of the differences between the diagnostic groups.…”
Section: Discussionmentioning
confidence: 67%
“…Second, volume measurement using MRI has a possible inherent bias of over-or underestimation in term of precise delineation and quantification. The ranges of the hippocampal subfield volumes acquired by the Winterburn atlas in this study might be different from previous data obtained by manual segmentation, owing to labeling protocol differences [36]. Third, the relatively small number of patients could affect the power of the study to detect all of the differences between the diagnostic groups.…”
Section: Discussionmentioning
confidence: 67%
“…Fifth, this study used automated hippocampal subfield segmentation using FreeSurfer version 6.0.0 instead of another popular tool, volBrain, known for its shorter processing time. Moreover, a comparative study demonstrated an association in terms of hippocampal subfield volumes between these 2 segmentation tools . Recently, more advanced methodologies, such as machine learning, may offer improved segmentation accuracy .…”
Section: Discussionmentioning
confidence: 99%
“…Though, recent studies on the hippocampal subfield volumes used high resolution T2-weighted images [ 55 , 56 ], we selected T1-weighted images for two main reasons. First, several previous studies conducted their hippocampal subfield automated segmentation using T1-weighted images, which may be helpful for us to validate our findings with previous studies due to commonality in the type of neuroimaging.…”
Section: Discussionmentioning
confidence: 99%